Barometers Behaving Badly I: Assessing the Influence of Analytical and Experimental Uncertainty on Clinopyroxene Thermobarometry Calculations at Crustal Conditions - Wieser, Penny E; Kent, Adam J R; Till, Christy B; Donovan, John; Neave, David A; Blatter, Dawnika L; Krawczynski, Michael J (Journal of petrology, 2023)
Abstract The composition of clinopyroxene and clinopyroxene-liquid (Cpx-Liq) pairs are frequently used to calculate crystallization/equilibration pressures in igneous systems. While canonical uncertainties are often assigned to calculated pressures based on fits to calibration or test datasets, the sources of these uncertainties (and thus ways to reduce them) have not been rigorously assessed. We show that considerable uncertainties in calculated pressures arise from analytical error associated with Electron Probe Microanalyser (EPMA) measurements of Cpx. Specifically, low X-ray counts during analysis of elements with concentrations <1 wt% resulting from insufficient count times and/or low beam currents yield highly imprecise measurements (1σ errors of 10–40% for Na2O). Low analytical precision propagates into the calculation of pressure-sensitive mineral components such as jadeite. Using Monte Carlo approaches, we demonstrate that elemental variation resulting from analytical precision alone generates pressures spanning ~4 kbar (~15 km) for a single Cpx and ~6 kbar for a single Cpx-Liq pair using popular barometry expressions. In addition, analytical uncertainties in mineral compositions produce highly correlated arrays between pressure and temperature that have been previously attributed to transcrustal magma storage. Before invoking such geological interpretations, a more mundane origin from analytical imprecision must be ruled out. Most importantly, low analytical precision does not just affect the application of barometers to natural systems; it has also affected characterization of Cpx in experimental products used to calibrate and test barometers. The impact of poor precision on each individual measurement is often magnified by the small number of measurements made within experimental charges, meaning that low analytical precision and true variability in mineral compositions have not been sufficiently mediated by averaging multiple EPMA analyses. We compile the number of Cpx measurements performed in N = 307 experiments used to calibrate existing barometers, and N = 490 new experiments, finding ~45% of experiment charges were characterized by ≤5 individual Cpx analyses. Insufficient characterization of the true composition of experimental phases likely accounts for the fact that all Cpx-based barometers exhibit large errors (± 3 kbar) when tested using global experimental datasets. We suggest specific changes to analytical and experimental protocols, such as increased count times and/or higher beam currents when measuring low concentration elements in relatively beam resistant Cpx in experiments and natural samples. We also advocate for increasing the number of analyses per experimental charge, resolving interlaboratory analytical offsets and improving data reporting. Implementing these changes is essential to produce a more robust dataset to calibrate and test the next generation of more precise and accurate Cpx-based barometers. In turn, this will enable more rigorous investigation of magma storage geometries in a variety of tectonic settings (e.g. distinguishing true transcrustal storage vs. storage in discrete reservoirs).